1996
DOI: 10.1007/bf01586186
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of methicillin-resistantStaphylococcus aureus on the basis of protein A gene polymorphism

Abstract: The polymorphic X-region of the protein A gene (spa) was used for molecular typing of methicillin-resistant Staphylococcus aureus (MRSA) strains. The X-region is characterized by a variable number (between 3 and 15) of small repeats. DNA sequencing of MRSA strains revealed 25 distinct repeats. Analysis of MRSA strains grown in vitro and in vivo revealed that the X-region was sufficiently stable for epidemiologic typing of MRSA strains. Spa typing of MRSA strains was compared to phage typing and, in general, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
236
3
12

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(266 citation statements)
references
References 7 publications
15
236
3
12
Order By: Relevance
“…The use of M13-sequence tagged amplicons in combination with M13-specific primers has been described for sequencing of Staphylococcus aureus protein A-gene (Spa-typing) amplicons [24] Our results convincingly demonstrate that this approach when employing a similar technique using SP6 and T7-specific sequencing primers for bi-directional sequencing of SP6 and T7-sequence tagged universal bla SHV-amplicons allowed for an unequivocal discrimination between bla SHV, bla LEN and bla OKP genes. The sequencing approach also confirmed that the apparent heterozygosity occurring at certain positions in the DNAsequences were due to heterozygosity caused by the simultaneous presence of bla SHV allelic variants.…”
Section: Discussionsupporting
confidence: 57%
“…The use of M13-sequence tagged amplicons in combination with M13-specific primers has been described for sequencing of Staphylococcus aureus protein A-gene (Spa-typing) amplicons [24] Our results convincingly demonstrate that this approach when employing a similar technique using SP6 and T7-specific sequencing primers for bi-directional sequencing of SP6 and T7-sequence tagged universal bla SHV-amplicons allowed for an unequivocal discrimination between bla SHV, bla LEN and bla OKP genes. The sequencing approach also confirmed that the apparent heterozygosity occurring at certain positions in the DNAsequences were due to heterozygosity caused by the simultaneous presence of bla SHV allelic variants.…”
Section: Discussionsupporting
confidence: 57%
“…It was shown that some epidemic and nonepidemic MRSA isolates could be discriminated on the basis of protein A gene polymorphism. However, the relationship between virulence and increased number of protein A repeat domains is unclear [18].…”
Section: Discussionmentioning
confidence: 99%
“…The highly adherent Staphylococcus aureus strain Cowan I is known to produce higher amounts of protein A than the low-adhering Wood 46 [22] and is estimated to contain 80,000 IgG binding sites per organism [41]. Freney et al [42] found that epidemic strains of MRSA had increased Protein A gene polymorphism, but van Belkum et al, [43] found no relation between gene polymorphism or protein A expression and colonisation of nasal epithelium. Poston et al [22] demonstrated that mec -agr -and spa -mutants of a spa + MRSA strain had less protein A and adhered less well to cell lines.…”
Section: Discussionmentioning
confidence: 99%